DIGITAL REDESIGN OF TRADITIONAL CHINESE TEXTILE PATTERNS: A SYNTHESIS OF NATIONAL TRADITIONS AND INNOVATIONS - HUO, DONGZE; SKLIARENKO , N.V. (Art and Design, 2024)
Purpose: the study explores the complexity of digitally transforming ancient Chinese textile patterns and allows identifying the stages of its digital redesign, blending national tradition craftsmanship with contemporary intellect. Methodology. A Systematic Exploration of Digital Redesign for Traditional Chinese Textile Patterns presents a methodical approach to investigating the potential of digitally redesigning traditional Chinese textiles. Using the method of historical and retrospective analysis provides a study of the history and origin of cultural references to traditional patterns. Art historical analysis of traditional ancient patterns requires researchers to make full use of previous records from history, literature, and visual works in order to understand the corresponding culture, social condition, and artistic world related to these patterns. Methods Archival research, Stylistic analysis, and Iconographic analysis and methods of digital redesign allow to outline ways of integrating traditional motifs into design practices, demonstrate their adaptability and ability to rethink their use in a digital environment. Forecasting method demonstrates the universal appeal of Chinese textile patterns in fostering creative bridges that uphold culture and promote good designs without boundaries. Results. It is proved in the work that traditional Chinese textile patterns have undergone changes over time, yet they have not entirely vanished in their transformation. This study outlines the author’s approach to manufacturing innovation, which involves a structured, holistic process for producing contemporary designs using traditional national textile motifs, based on a redraft of cultural patterns. Five key stages of redesign of Chinese textile patterns are highlighted, such as Traditional Inspirations, Adaptation and Simplifications, Integration into Design Practices, Digital Transformation and Cross-Cultural Fusion. These stages extend beyond Chinese textiles, serving as a universal model for product development that incorporates traditional elements of national heritage. It ensures a seamless fusion of tradition and contemporary design. It also underscores the strength and durability of Chinese textile heritage, which illustrates its capability to pass down creativity for new forms in a world that is rapidly changing. The results highlight the importance of maintaining heritage while using modern technology. Scientific novelty. This work describes an original method of digital re-design for traditional textile patterns, based on a five-phased model. The research links each stage with its core and talks about how their commonality has significance to the more general conversation of cultural heritage preservation in contemporary design. It was proved for the first time that they serve as the foundation for a universal redesign protocol, equipping designers worldwide with knowledge and tools that enhance both cultural and digital design studies.